PENURUNNYA KECEMASAN TIKUS OVARIEKTOMI SETELAH LATIHAN INVERVAL DENGAN INTENSITAS TINGGI - Saidah Rauf (Poltekkes Kemenkes Maluku, 2018)
It is well established that a decrease of estrogen during natural or surgical menopause (ovariectomy)could influence female anxiety behaviour both in human and animal experiments. Several studies haveproved that exercise act as a potential therapy to reduce depression and anxiety behaviours. The currentstudy analyzed the effects of High-Intensity Interval Exercise (HIIE) to anxiety-related behaviours ofrats after long-term ovaries removal. Fifteen Sprague-Dawley rats (twelve weeks old) were used in thisstudy. All rats were divided into sham-operated, ovariectomy, and ovariectomy with HIIE (OVXHIIE). The HIIE group was treated for 7 weeks of interval exercise that started after twelve weeks ofovariectomized using treadmill. Anxiety related behaviour were represented by frequencies toentrances centre arena, freezing and grooming duration on open field test. A significant decrease(p<0.05) in the frequencies to enter open arena was detected in ovariectomized rats compared to shamand ovariectomy with HIIE, while reversed effect has observed in freezing duration. The present resultsshow that HIIE may help to counteract the ovariectomized effect on anxiety-related behaviours of rats.The HIIE may become the promising therapy to treat anxiety behaviour on menopause condition. Keywords: Anxiety, interval exercise, ovariectomy, menopause